Application of chitosan- and alginate-modified biochars in promoting the resistance to paddy soil acidification and immobilization of soil cadmium. (15th November 2022) - He, Xian; Nkoh, Jackson Nkoh; Shi, Ren-yong; Xu, Ren-kou
Abstract: To develop more green, practical and efficient biochar amendments for acidic soils, chitosan-modified biochar (CRB) and alginate-modified biochar (ARB) were prepared, and their effects on promoting soil pH buffering capacity (pHBC) and immobilizing cadmium (Cd) in the paddy soils were investigated through indoor incubation experiments. The results of Fourier transform infrared spectroscopy and Boehm titration indicated that the introduction of chitosan and sodium alginate effectively amplified the functional groups of the biochar, and improved acid buffering capacity of the biochar. Since there was a plateau region between pH 4.5 and 5.5 in acid-base titration curve of the CRB, adding this biochar to acidic paddy soils apparently improved the pHBC and enhanced the acidification resistance of the paddy soils. The addition of ARB enhanced the reduction reactions during submerging and weakened the oxidation reactions during draining, thus retarded the decline of paddy soil pH during drainage. Furthermore, the pH of the paddy soils with ARB addition was higher at the end of draining, which reduced the activity of soil Cd. Considering the environmental sustainability of chitosan and sodium alginate and convenience of preparation method, biochars modified with these two materials provided alternatives for acidic paddy soil amelioration and heavy metal immobilization. However, the additional experiments should be conducted under field conditions to confirm practical application effects in the future. Graphical abstract: Image 1 Highlights: Chitosan and alginate effectively amplified the functional groups on biochar. The two modified biochars were environmentally sustainable. The preparation methods of the two modified biochars were convenient. Chitosan-modified biochar had potential in acidic paddy soil amelioration. Alginate-modified biochar had advantages in heavy metal immobilization.